A perylene diimide (PDI)-based small molecule with tetrahedral configuration as a non-fullerene acceptor for organic solar cells1. Issue 18 (14th May 2015) - Chen, Wangqiao; Yang, Xuan; Long, Guankui; Wan, Xiangjian; Chen, Yongsheng; Zhang, Qichun
<x xml:space="preserve">Abstract</x> In this paper, a new perylene diimide (PDI)-based acceptor Me-PDI4 with tetrahedral configuration (or 3D) has been synthesized and characterized.